StainNet: A Fast and Robust Stain Normalization Network - Kang, Hongtao; Luo, Die; Feng, Weihua; Zeng, Shaoqun; Quan, Tingwei; Hu, Junbo; Liu, Xiuli (Frontiers in Medicine, 2021)
Stain normalization often refers to transferring the color distribution to the target image and has been widely used in biomedical image analysis. The conventional stain normalization usually achieves through a pixel-by-pixel color mapping model, which depends on one reference image, and it is hardly to achieve accurately the style transformation between image datasets. In principle, this difficulty can be well solved by the deep learning-based methods e, whereas, its complicated structure results in the low computational efficiency and artifacts in the style transformation, which has restricted the practical application. Here, we use distillation learning to reduce the complexity of deep learning methods and a fast and robust network called StainNet to learn the color mapping between the source image and target image. StainNet can learn the color mapping relationship from a whole dataset and adjust the color value in a pixel-to-pixel manner. The pixel-to-pixel manner restricts the network size and avoids artifacts in the style transformation. The results on the cytopathology and histopathology datasets show that StainNet can achieve comparable performance to the deep learning-based methods. Computation results demonstrate StainNet is more than 40 times faster than StainGAN and can normalize a 100,000x100,000 whole slide image in 40 seconds.